Skrining Fitokimia dan Uji Penghambatan Aktivitas alfa-glukosidase pada Ekstrak Etanol dari Beberapa Tanaman yang Digunakan sebagai Obat Antidiabetes - Munim, Abdul; Azizahwati, Azizahwati; Andriani, Ayu (UI Scholars Hub, 2012)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglicemia and associated with abnormalities in carbohydrate, fat, and protein metabolisms. Patients with DM in the world continue to increase along with population growths. Starting from this condition, searching for sources of DM treatment is always performed. One therapy of DM is a-glucosidase inhibitor. a-Glucosidase is an enzyme that can break down a complex carbohydrate into simple sugar. lhe inhibiton of this enzyme can retard the rate of carbohydrate digestion resulting in a delay in glucose absorption. The purpose of this studywas to identify the content of chemical compound and to test the a-glucosidase inhibitory activity in ethanolic extracts of some plants used as antidiabetic. a-Glucosidase inhibitory activity test carried out by spectrophotometric method. The simplisia powder was extracted by reflux using 80% ethanol. Based on a-glucosidase inhibitory activity test, all the plant extracts were active in inhibiting a-glucosidase. lhe three most active extracts were Ceiba pentandra (L.) Gaetern bark extract, Saccharum offcinarum root extract, and Persea americana Mill. bark extract with IC50 of 5.16, 10.35 and 10.83 ppm, respectively. They contain glycoside, tannin, and saponin. The test results of the kinetics enzyme inhibition showed that Randu bark extract had competitive inhibitory activity.